1997
DOI: 10.1073/pnas.94.25.13504
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-mediated repression of nuclear factor-κBdependent transcription involves direct interference with transactivation

Abstract: Glucocorticoids exert multiple anti-inf lammatory activities, one of which is the inhibition of transcription dependent on the nuclear factor (NF)-B. It has been suggested that the effect of dexamethasone (DEX), a glucocorticoid analog, is attributed to an increased production of the inhibitory IB molecule, which in turn would bind and remove activated, DNA-bound NF-B complexes in the cell nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
219
2
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(232 citation statements)
references
References 65 publications
10
219
2
1
Order By: Relevance
“…Consistent with this, the protein synthesis inhibitor cycloheximide (CHX) did not diminish the inhibitory effect of dex on expression of IL-6, intracellular adhesion molecule (ICAM)-1 or COX-2 mRNAs (De Bosscher et al, 1997;Wissink et al, 1998). In other studies, CHX blocked the GCmediated suppression of urokinase plasminogen activator, COX-2 and CXCL8 mRNA (Chang et al, 2001;Chaudhary and Avioli, 1996;Chivers et al, 2006;Henderson and Kefford, 1993;Newton et al, 1998;Tobler et al, 1992).…”
Section: Inhibitory Effects Of Gc Do Not Require De Novo Gene Expressmentioning
confidence: 80%
See 2 more Smart Citations
“…Consistent with this, the protein synthesis inhibitor cycloheximide (CHX) did not diminish the inhibitory effect of dex on expression of IL-6, intracellular adhesion molecule (ICAM)-1 or COX-2 mRNAs (De Bosscher et al, 1997;Wissink et al, 1998). In other studies, CHX blocked the GCmediated suppression of urokinase plasminogen activator, COX-2 and CXCL8 mRNA (Chang et al, 2001;Chaudhary and Avioli, 1996;Chivers et al, 2006;Henderson and Kefford, 1993;Newton et al, 1998;Tobler et al, 1992).…”
Section: Inhibitory Effects Of Gc Do Not Require De Novo Gene Expressmentioning
confidence: 80%
“…In some studies anti-inflammatory effects of GCs were not accompanied by changes in DNA-binding activity of NFκB as measured by electrophoretic mobility shift assay (Brostjan et al, 1996;De Bosscher et al, 1997;Hofmann et al, 1998;Nissen and Yamamoto, 2000;Ray et al, 1997;Wissink et al, 1998). However, in other cases GCs were found to inhibit NFκB activation as measured by the same assay (Eberhardt et al, 2002;Goppelt-Struebe et al, 2000;Kurata and Yamamoto, 1999;Kurokouchi et al, 2000;Ma et al, 2004;Mukaida et al, 1994;Vital et al, 2003).…”
Section: Gc-dependent Inhibition Of Gene Expression Is Not Accompaniementioning
confidence: 99%
See 1 more Smart Citation
“…Steroidmediated repression of NF-B-dependent genes has also been demonstrated in fibroblasts, although I B protein levels remained unchanged. It has been suggested that direct protein-protein interactions between the activated glucocorticoid receptor and the p65 subunit of NF-B can mediate suppression of NF-Bdependent transcriptional activity (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that glucocorticoid receptor activation may repress transcription and/or splicing of NCAM (Colwell et al, 1992;Quandt et al, 1995;De Bosscher et al, 1997;Simpson and Morris, 2000;Datson et al, 2001;Karin and Chang, 2001;Takeuchi and Fukunaga, 2003;Sandi, 2004).…”
Section: Exposure To Stress During Juvenility Alters Emotional Responmentioning
confidence: 99%